Influence of thickness on the optical properties of Sb doped ZnO thin films - Hoq, E; Bhuiyan, MRA; Begum, J (Journal of Bangladesh Academy of Sciences, 2014)
Sb doped ZnO thin films having various thicknesses have been prepared onto glass substrate by using thermal evaporation method. The atomic compositions of the grown films have been determined by Energy Dispersive Analysis of X-ray (EDAX) method. The optical properties were measured by using a UV-VIS-NIR spectrophotometer (300 to 2500 nm). The EDAX analysis revealed that Sb is doped into the ZnO films. Optical properties showed high absorption coefficient (~105/cm) that direct allowed transition band gap. The optical band gap of the ZnO thin films became reduced due to the doping of Sb. DOI: http://dx.doi.org/10.3329/jbas.v38i1.20217 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 93-96, 2014